Diversity in Study Habits of Formal and Non Formal Students: A Case of F.G Education College and Allama Iqbal Open University Islamabad: Ehsan Mahmood , Hamid Ali Nadeem , Irfan Haider (PJDOL, 2023)
This study aimed to determine and compare study habits of formal and non-formal students at post graduate level. The study was conducted in Federal Government Education College Islamabad and four regions of Allama Iqbal Open University Islamabad. T